Similar Effects of Acute Resistance Exercise on Carotid Stiffness in Males and Females - Grigoriadis, Georgios; Rosenberg, Alexander J.; Lefferts, Wesley K.; Wee, Sang Ouk; Schroeder, Elizabeth C; Baynard, Tracy (International Journal of Sports Medicine, 2020)
Sex differences exist in vascular responses to blood pressure perturbations, such as resistance exercise. Increases in aortic stiffness following acute resistance exercise appear different between sexes, with attenuated increases in females vs. males. Whether sex differences exist in carotid stiffness, following resistance exercise is unknown. This study sought to examine sex differences in carotid stiffness, aortic stiffness, and hemodynamics following acute resistance exercise. Thirty-five participants (18 male) completed 3 sets of 10 repetitions of maximal isokinetic knee extension/flexion. Aortic stiffness and hemodynamics were estimated using an automated oscillometric blood pressure monitor at baseline, 5- and 30-min post-exercise. Carotid stiffness was assessed by β-stiffness index, pressure-strain elastic modulus and arterial compliance using ultrasonography. Resistance exercise increased aortic stiffness, mean and systolic pressure at 5-min (p<0.01), and pressure-strain elastic modulus at 5-min in both sexes (p<0.05). Arterial compliance decreased at 5- and 30-min post exercise in both sexes (p<0.01). No interaction effects were detected in carotid stiffness, aortic stiffness, and hemodynamics, indicating similar vascular responses between sexes. Our findings indicate that the large arteries appear to stiffen similarly following resistance exercise in males and females when presented with similar blood pressure responses.
Keywords: arterial stiffness; resistance exercise; sex differences